Activation of Rac1 promotes Hedgehog-mediated acquisition of the myofibroblastic phenotype in rat and human hepatic stellate cells - Choi, Steve S. (2010)
Hepatic accumulation of myofibroblastic hepatic stellate cells (MF-HSC) is pivotal in the pathogenesis of cirrhosis. Two events are necessary for MF-HSC to accumulate in damaged livers: transition of resident, quiescent HSC (Q-HSC) to MF-HSC, and expansion of MF-HSC numbers via increased proliferation and/or reduced apoptosis. Our group has identified two novel mediators of MF-HSC accumulation: Rac1 and Hedgehog (Hh). It is unclear if Rac1 and Hh interact to regulate the accumulation of MF-HSC. We evaluated the hypothesis that Rac1 promotes the activation of the Hh pathway, thereby stimulating signals that promote transition of Q-HSC into MF-HSC, and that enhance the viability of MF-HSC. Using both in vitro and in vivo model systems, Rac1 activity was manipulated via adenoviral vector-mediated delivery of constitutively active or dominant-negative Rac1. Rac1-transgenic mice with targeted myofibroblast expression of a mutated human rac1 transgene that produces constitutively active Rac1 were also examined. Results in all models demonstrated that activating Rac1 in HSC enhanced Hh signaling, promoted acquisition/maintenance of the MF-HSC phenotype, increased MF-HSC viability, and exacerbated fibrogenesis. Conversely, inhibiting Rac1 with dominant-negative Rac1 reversed these effects in all systems examined. Pharmacologic manipulation of Hh signaling demonstrated that pro-fibrogenic actions of Rac1 were mediated by its ability to activate Hh pathway-dependent mechanisms that stimulated myofibroblastic transition of HSC and enhanced MF-HSC viability. In conclusion, these findings demonstrate that interactions between Rac1 and the Hh pathway control the size of MF-HSC populations and have important implications for the pathogenesis of cirrhosis.